IMPLEMENTATION OF STUDENT CHARACTER EDUCATION THROUGH LEADERSHIP CAMP AND SOLO CAMP PROGRAM: STUDY AT SMA NEGERI SUMATERA SELATAN - Sari, Dian Ratna; Novianto, Andreas; Kusuma, Iswan Djati (BIOCHEPHY: Journal of Science Education, 2025)
The implementation of character education has different models or methods in terms of approach and practice, especially at schools. The same thing is done by SMAN Sumatera Selatan as an innovation in shaping the character of its students by holding Leadership and Solo Camp activities which are routinely carried out to shape the character of its students. To observe this, the research method used was a descriptive qualitative approach with the unit of analysis being a study in one of the areas of high school which is SMAN Sumatera Selatan. Determining the informants was carried out by snowballing using 10 informants. The data collection technique uses primary data obtained from direct observation and interviews using interview guidelines. This article also uses secondary data in the form of historical literature or literature studies. The results of this research state that SMAN Sumatera Selatan is a boarding school that implements routine boarding activities every day. Apart from that, each student's activity has been arranged and is in accordance with their interests and talents, this supports the Merdeka curriculum school standards and is in accordance with the Vision and Mission of SMAN Sumatera Selatan to form national leaders and is supported by nine core values, which can work in synergy. and sustainable. On the other hand, the Leadership Program and Solo Camp can be a forum and the first step in improving leadership character and survival spirit in the field. This is one of the superior programs for character building at SMAN Sumatera Selatan.